A review of normal radiographical variants commonly mistaken for pathological findings in horses. (3rd April 2019) - Hinkle, F. E.; Johnson, S. A.; Selberg, K. T.; Barrett, M. F.
Summary: A normal variant is an atypical finding present in a percentage of the population that generally has no clinical significance and is considered within the spectrum of normal findings. Normal variants are recognised upon gross anatomical dissection and also observed radiographically. Understanding the range of normal variants is essential for proper radiographical interpretation. This ensures that these variants are not mistaken for pathological lesions and helps avoid radiographical misdiagnosis. Common sites of normal anatomical variation in the foot, pastern, carpus, tarsus, elbow, shoulder and axial skeleton are reviewed.